Study of quasi-periodic oscillation in X-ray lightcurve of BL Lac using Swift/XRT - Bhusal, Nabin; Khatiwada, Manil; Khanal, Bishal (Kathmandu University Journal of Science Engineering and Technology, 2025)
We analyzed 17 years (2005–2022) of X-ray time series data from the BL LAC object, a type of active galactic nucleus, using open data from the Neil Gehrels Swift Observatory. Data with exposure times exceeding 1000 seconds in photon-counting (PC) and windowed timing (WT) modes were processed using HEASoft, software. Rapid XRT data analysis revealed quasi-periodic oscillation (QPO) in BL LAC, a bright source potentially influenced by complex motions, such as those of a supermassive binary black hole system. We employed power spectral density (PSD), epoch folding, and autocorrelation function (ACF) methods to investigate periodicity. The light curve exhibited red noise characteristics, and frequency domain analysis confirmed a 1.593 hour QPO. These findings contribute to understanding the variability and potential binary nature of BL LAC objects.